Специфіка особистісно-професійної здійсненності поліцейських з різним стажем роботи в поліції - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Пономаренко (Посохова) Яна Сергіївна (Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.14. - С. 55-61, 2022)
Визначено, що особистісно-професійна здійсненність – це безперервний простір особистісної реалізованості суб'єкта в житті та самореалізація в професійній діяльності, які в континуумі розкривають унікальний напрям життєздійснення особистості. Одним з ефективних та дієвих факторів у подоланні негативного професійного досвіду та чинником у формуванні стійкості виступає розвинута особистісно-професійна здійсненність у поліцейських. Вивчено специфіку особистісно-професійної здійсненності поліцейських з різним стажем роботи в поліції.

The article presents a study of the personal and professional fulfilment of police officers who have different years of experience in the police. Personal and professional fulfilment (PPF) is a continuous space of the subject's personal realization in life and self-realization in professional activities, which in the continuum reveal a unique direction of the individual's life realization. One of the effective and efficient factors in overcoming negative professional experience and a factor in the formation of resilience is the developed personal and professional fulfilment of police officers. The purpose of the study was based on the study of the specifics of the personal and professional fulfilment of police officers with different years of experience in the police. The sample consisted of 90 policemen. The distribution of groups took place on the basis of the length of service in the police. The first group, work experience from 3 to 5 years - 20 people. The second group, work experience from 5 to 10 years - 25 people. The third group, work experience from 1 to 20 years - 30 people. The fourth group, more than 20 years of experience - 15 people. To achieve the goal, the author's method "Diagnostics of the personality's-professional fulfillmentity of police officers" was used. The results of the study were subjected to a quantitative analysis using Student`s t-criterion for independent groups. It has been empirically established that police officers with 3-5 years of experience have a high level of PPF. They are ready to change, improve, overcome difficulties and achieve success. Police officers with 5-10 years of experience have an average level of PPF, which affects their ability to develop, is expressed through satisfaction with their life and opportunities in the profession. They actively apply their own experience in decision-making and are emotionally stable compared to other groups. Police officers with 10-20 years of experience also have an average level of PPF, they are already self-determined in life, they are clearly aware of their needs, they know how to overcome difficulties, but it is difficult for them to properly plan their further actions. Policemen with more than 20 years of experience have an average level of PPF, which indicates their mature attitude towards their profession, they still set goals for themselves and realize them. At the same time, it is difficult for the fourth group to perceive innovations and changes, as well as to apply them in practice.

Определено, что личностно-профессиональная осуществимость – это непрерывное пространство личностной реализуемости субъекта в жизни и самореализация в профессиональной деятельности, которые в континууме раскрывают уникальное направление жизнеосуществления личности. Одним из эффективных и действенных факторов в преодолении негативного профессионального опыта и фактором в формировании устойчивости выступает развитая личностно-профессиональная осуществимость полицейских. Изучена специфика личностно-профессиональной осуществимости полицейских с разным стажем работы в полиции.
Specifics of personal and professional fulfilment of police officers with different years of experience in the police
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; поліцейські; police officers; полицейские; особистісно-професійна здійсненність; personal and professional feasibility; личностно-профессиональная осуществимость; стаж роботи; work experience; стаж работы; професійний досвід; professional experience; профессиональный опыт; реалізованість; realizability; реализованность